2005
DOI: 10.1007/s00705-005-0521-1
|View full text |Cite
|
Sign up to set email alerts
|

HBx protein of hepatitis B virus (HBV) can form complex with mitochondrial HSP60 and HSP70

Abstract: HBx, a transcriptional transactivating protein of hepatitis B virus (HBV), is required for viral infection and has been implicated in virus-mediated liver oncogenesis. However, the molecular mechanism for its influence on cell remains largely unknown. It was proved that HBx need the help of host cell proteins to exert its function by binding to them. During purifying of GSTX (fusion protein of GST and HBx) expressed in E. coli, we found that it can bind specifically with GrpE (HSP60) and DnaK (HSP70) of E. col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 19 publications
3
41
0
Order By: Relevance
“…It is also indicated that by causing the loss of mitochondrial membrane potential, HBx protein induces mitochondria-dependent apoptosis (Shirakata and Koike, 2003). Furthermore, HBx protein can form a complex with mitochondrial proteins, HSP60 and HSP70 that exerts effects on mitochondria-dependent apoptosis (Zhang et al, 2005a). HBx protein also may alter mitochondrial function by association with a member of the family of human mitochondrial voltage-dependent anion channel (HVDAC3) (Rahmani et al, 2000).…”
Section: Pro-apoptotic Effects Of Hbx Proteinmentioning
confidence: 99%
“…It is also indicated that by causing the loss of mitochondrial membrane potential, HBx protein induces mitochondria-dependent apoptosis (Shirakata and Koike, 2003). Furthermore, HBx protein can form a complex with mitochondrial proteins, HSP60 and HSP70 that exerts effects on mitochondria-dependent apoptosis (Zhang et al, 2005a). HBx protein also may alter mitochondrial function by association with a member of the family of human mitochondrial voltage-dependent anion channel (HVDAC3) (Rahmani et al, 2000).…”
Section: Pro-apoptotic Effects Of Hbx Proteinmentioning
confidence: 99%
“…These interactions seem to alter the trans membrane potential and enhance HBx-mediated apoptosis. (38)(39)(40)(41) The biological role of HBx in HBV replication. X ORF is phylogenically conserved among mammalian hepadnavirus genomes, strongly indicating that HBx has some biological roles to facilitate or augment the viral life cycle.…”
Section: −10mentioning
confidence: 99%
“…HBx exerts powerful effects on mitochondria either directly owing to their channel-forming activity or indirectly through interactions with endogenous channels (Takada et al, 1999;Henkler et al, 2001;Lee et al, 2004). HBx reportedly interacts with at least two mitochondrial proteins, namely heat-shock protein 60 and 70 (Tanaka et al, 2004;Zhang et al, 2005b) and the VDAC isoform VDAC3 (Rahmani et al, 2000;Kim, 2005).…”
Section: Hbxmentioning
confidence: 99%